Characterization of promising natural blue pigment from Vaccinium bracteatum thunb. leaves: Insights of the stability and the inhibition of α-amylase. (1st October 2020) - Fan, Mingcong; Lian, Weijia; Li, Tingting; Rao, Zhiming; Li, Yan; Qian, Haifeng; Zhang, Hui; Qi, Xiguang; Wang, Li
Highlights: A concise method of blue pigment by Vaccinium bracteatum thunb. leaves was proposed. The blue pigment was prone to stable in the moderate acidic system. The blue pigment showed high retention rate in simulated digestion period in vitro . The blue pigment inhibited the activity of pancreatic α-amylase (IC50  = 2.915 mg/mL). The biological structure of α-amylase was change by the blue pigment. Abstract: A concise method of natural blue pigment from Vaccinium bracteatum thunb. leaves (VBTL) was proposed firstly in this research. The potential properties of new pigment source needed to be assessed for further application. During the shelf life and thermal-accelerated storage, the blue pigment was prone to stable in the mildly acidic system, which was observed retention of 35.85% for storage of 12 weeks in pH 4.0. The 65% of blue pigment retained after the in vitro simulated digestion. The blue pigment exhibited inhibition effect on the pancreatic α-amylase (IC50  = 2.915 mg/mL). The analysis of inhibition kinetics indicated the blue pigment was an uncompetitive inhibitor. Through fluorescence quenching and circular dichroism study, the blue pigment inhibited α-amylase activity via the structural unfolding of α-amylase molecule and changing the secondary structure. These findings provided the new evidence of the digestion resistibility of VBTL pigment and the functional food – " Wu mi ".